Outgassing studies on thermal control coatings for micro‐satellites - Joshi, Sunil Chandrakant (2015)
Purpose – With the advent of micro‐satellites technology, passive thermal controls in the form of surface coatings have become important for onboard thermal management. The thermal coatings, however, suffer outgassing and mass loss due to their direct exposure to harsh thermal environment and high vacuum in space. The purpose of this paper is to discuss testing and evaluation on outgassing of AA6061‐T6 specimen surfaces treated with various types of anodized coatings of different thicknesses and the related mass loss before and after thermal exposure. Design/methodology/approach – Samples of chromic acid, polytetrafluroethylene polymer, and black‐ and brown‐colour anodized aluminum coupons were subjected to high vacuum (∼1×10−6 mbar), before and after thermal baking at 120°C. Spectrum analysis of the outgassed material to know their quantities and proportion was conducted subsequently using a Quadrupole mass analyzer. Findings – The surface coatings under study complied with the spacecraft requirements for the mass loss of less than 1 percent of the total mass of the coating material used for that surface. The mass spectrum analysis of the outgassed material indicated that the majority of the coating mass loss was on account of water vapours and organic solvents like ethylene. Practical implications – These results provided a good insight into the reliability of the coating materials studied and the bonding between the aluminum substrates and the coatings. Originality/value – The coatings and the technology needed for their application on aluminum are readily available. The present work on outgassing and mass loss in a simulated space environment will provide useful insight on their usage for micro‐satellites.